IITA Valentine's Day Message - International Institute of Tropical Agriculture (International Institute of Tropical Agriculture, 2019)
The International Institute of Tropical Agriculture (IITA) is a non-profit institution that generates agricultural innovations to meet Africa’s most pressing challenges of hunger, malnutrition, poverty,and natural resource degradation. Working with various partners across sub-Saharan Africa, we improve livelihoods, enhance food and nutrition security, increase employment, and preserve natural resource integrity.